Zoobreak / 2 - Korman, Gordon (Swindle, 2009)
After a class trip to a floating zoo where animals are mistreated and Savannah's missing pet monkey is found in a cage, Long Island sixth-grader Griffin Bing and his band of misfits plan a rescue.